Spreminjanje sistema blaginje v postsocialističnih državah in primer Slovenije - Mandič, Srna (Teorija in praksa, 2012)
The article examines the changes occurring in the welfare systems of post-socialist Central European countries, with a particular focus on Slovenia. First, an overview is given of wider debates about the transition and the transitional welfare reforms, highlighting the impact of distributive struggles on the course of the reforms. By summarising findings on the outcomes of major reforms in the region, it is shown how the long-term concerns about demographic ageing have been overshadowed by the current distributive struggles. This is most notably the case with the pension and long-term care systems. Long-term care is highlighted due to it lagging behindin the modernisation of services and introduction of insurance schemes to cover costs. It is argued that long-term care, as a policy domain, has beenspecifically strongly victimised by the transition; the system is not being allowed to respond to the newly emerged needs, with old-age care thus largely remaining locked within the private sphere, as a private matter subject to family support.
Keywords: Država blaginje; Transition; Tranzicija; Welfare; Family; Blaginja; Reforme; The elderly; Slovenia; Družina; Ostareli; Slovenija; postsocializem